Becoming an empowered parent. How do parents successfully take up their role as a collaborative partner in their child's specialist care?. (March 2021) - Reeder, Jim; Morris, Jane
The purpose of this article is to offer an improved understanding of how parents of children with long-term disabilities are empowered to successfully take up their role as decision-making partners in the design and delivery of the care of their child. The intention is to stimulate dialogue, encourage reflection and provide practical suggestions for health professionals working with children and their families. The reported findings are from a study which was guided by a constructivist grounded theory methodology. This involved an iterative process of repeated cycles of data collection and analysis, which comprised 12 semi-structured, in-depth interviews with 14 parents of children accessing paediatric services within a single National Health Service Trust. A novel model, explaining how the power im/balance and the perceived state of the therapeutic relationship influence how successfully a parent takes up their position in the collaborative partnership, is presented and discussed. It is suggested that by thoughtfully addressing the traditional hierarchy that exists within healthcare, health professionals might facilitate the development of a 'truly' therapeutic relationship, which can help promote parental empowerment.